Tribune opinion: University, Science and Social Economy - Julià, Juan Francisco; Melià, Elena; Lajara, Natalia (REVESCO. Revista de Estudios Cooperativos, 2015)
The current Spanish university system has turned out to be considered a high-quality environment in all its universities. The University has assigned three key missions: education, research and transfer to society. We can say that performs in a more than reasonable both teaching and research, proof of this are the positions obtained in international rankings, despite not yet put any in top positions despite having competitive disadvantages of character structural over other systems such as funding education. However, in the field of transfer the Spanish University has a major challenge because as indicators exposed at work (patents, entrepreneurship, spin-offs) the margin of improvement is still wide. In relation to the Social Economy within the university, it is found that the offer of training is reduced but so is the demand. It also becomes clear scientific production that is being developed in this field in recent years and is in line or even slightly above average compared to other similar areas.
Keywords: cooperatives; education; transfer